2003
DOI: 10.1152/japplphysiol.01088.2002
|View full text |Cite
|
Sign up to set email alerts
|

Spanish genetic admixture is associated with larger V̇o2 maxdecrement from sea level to 4,338 m in Peruvian Quechua

Abstract: Quechua in the Andes may be genetically adapted to altitude and able to resist decrements in maximal O2 consumption in hypoxia (DeltaVo2 max). This hypothesis was tested via repeated measures of Vo2 max (sea level vs. 4338 m) in 30 men of mixed Spanish and Quechua origins. Individual genetic admixture level (%Spanish ancestry) was estimated by using ancestry-informative DNA markers. Genetic admixture explained a significant proportion of the variability in DeltaVo2 max after control for covariate effects, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 47 publications
2
59
0
1
Order By: Relevance
“…In a relatively large study, Tibetans born and raised at high altitude (Tibetan descent) had higher near-maximal exercise Sa O 2 than Chinese residents at the same altitude (Chinese descent) who were moved there in adulthood and had lived at high altitude for Ͼ1 yr (27). A previously mentioned study (3) from La Paz finding a more efficient V E/V O 2 in residents of Aymara/Quechua than in individuals of European/North American descent also showed that the difference disappeared when the subjects of Indian descent were compared with two groups of European/North American immigrants born or arriving in La Paz before 18 yr of age (3). A potentially confounding factor would be non-Indian gene admixture in the high-altitude natives.…”
Section: Discussionmentioning
confidence: 92%
“…In a relatively large study, Tibetans born and raised at high altitude (Tibetan descent) had higher near-maximal exercise Sa O 2 than Chinese residents at the same altitude (Chinese descent) who were moved there in adulthood and had lived at high altitude for Ͼ1 yr (27). A previously mentioned study (3) from La Paz finding a more efficient V E/V O 2 in residents of Aymara/Quechua than in individuals of European/North American descent also showed that the difference disappeared when the subjects of Indian descent were compared with two groups of European/North American immigrants born or arriving in La Paz before 18 yr of age (3). A potentially confounding factor would be non-Indian gene admixture in the high-altitude natives.…”
Section: Discussionmentioning
confidence: 92%
“…Exercise differences in pulmonary gas exchange between altitude natives and lowlanders are also the result of genetic selection over millennia, since secondgeneration Tibetan lowlanders acclimatize to high altitude more quickly than Caucasians (Marconi et al, 2004). Thus both genetic and developmental adaptations contribute to the enhanced pulmonary gas exchange efficiency in altitude natives, with a likely predominance of the genetic over the developmental component (Brutsaert et al, 2003;Marconi et al, 2004).…”
Section: Effects Of Altitude Acclimatization On Pulmonary Gas Exchangementioning
confidence: 99%
“…Exercise studies were conducted in Cerro de Pasco. Previously published maximal oxygen consumption data from Lima are also presented here to demonstrate that cardiorespiratory fitness was not a confounding factor relative to the respiratory control studies (5). Again, subjects were tested in Cerro de Pasco after 10 -12 h of exposure to 4,338 m. To begin, V O2 and SaO 2 were measured at rest (5 min) with the subject seated.…”
Section: Methodsmentioning
confidence: 94%
“…This approach has been used recently to reveal ancestry associations with some complex disease traits in admixed populations (15,23,41,72), as well as ancestry associations with the V O 2 max decrement in Quechua (5). Admixture may also be exploited in future studies to map genes involved in complex traits or diseases that have a genetic basis and are known to differ significantly between parental populations using an approach known as admixture mapping (28,48).…”
Section: Discussionmentioning
confidence: 99%